V.1 - "Chatterjee, Sarajit Kumar" (New Delhi, 2008)
Attempts have been made in this study to present an over-all profile of the Scheduled Castes from different dimensions i.e., facts, figures and their interpretations, the policy of segregation of a sizable section of Indian population on the basis of caste.
Keywords: Anthropology